ETIKA PENDIDIKAN KEDOKTERAN: KETELADANAN DALAM PROFESIONALISME - Bernadetha Nadeak (Jurnal Dinamika Pendidikan, 2015)
This study presents a review on Medical Education Ethics: Modelling on Professionalism. The objective of this study was to review the ethich on medical education that focuses on competency attainment of medical education curriculum in Indonesia. It was conducted using library research where some books were read and reviewed in order to meet the purpose of this study, and the writer was the key instrument. The finding of this study is that ethics, morals, norms, values and professionalism in the field of medical are so important, that it is necessary to be integrated into the curriculum of medical education. Through the integration, it is expected to create graduates who are not only competent in their field knowledge, but also to have good behavior to be modelled in carrying out the profession of a doctor.Keywords : ethics, moral, norms, values, professionalism, curriculum, medical education, and model.